(untitled) (Nigerian Journal of Technology, 2016)
Dredging is a routine process necessary along waterways. This should be conducted in such a way that the quantity or volume of dredged materials can be determined for the purpose of costing and extent of the dredging. Therefore, the aim of this study is to compute the volume or stockpile of dredged materials using geospatial data. In order to obtain the geospatial data needed for the computation of the volume of the excavated material, pre-and post-dredged surveys of the study area were carried out. The three dimensional surfaces of both pre- and post-dredged surveys were produced from the acquired geospatial data. The volume of the stockpile computed from the pre- and post-dredged surveys is approximately 9732m3. The contour map and TIN were also produced. http://dx.doi.org/10.4314/njt.v35i4.3